Between the rural and the urban (the collection of Milo Urban’s novels Z tichého frontu [From the silent front], 1932) - Karol Csiba (Slovenska Literatura)
The collection of short prose by Milo Urban (1904 – 1982) Z tichého frontu. Časové rozprávky (From the silent front. Temporal tales) published in 1932 brought a selection of the author’s mostly magazine-published prose from the second half of the 1920s. The study recapitulates period critical and later literary-historical reflection on the book, revealing its broader socio-cultural context through parallels with Urban’s other work, especially his journalism and autobiographical prose. A key focus of the analysis is Urban’s depiction of the town-village relationship, presented as part of the modernist discourse in interwar Slovakia. Utilizing Roger Griffin’s concepts, the study examines the portrayal of disoriented individuals, whose lack of direction results from societal transformations and atomization. Another theme is the concept of ‘modernist nationalism,’ linked to the search for new certainties influencing human consciousness and sensibility. The study also addresses Urban’s ambivalent definitions of life, shaped by the relationship between regularity and coincidence, which are central themes in his novels.